A Delphi Evaluation of User Interface Design Guidelines: The Case of Arabic. (14th September 2022) - Al-Sa'di, Ahmed; Al-Samarraie, Hosam
Abstract : Due to the importance of design guidelines in facilitating user experience and promoting efficiency, it is essential to determine the effectiveness of certain design guidelines for a specific population. There have been a number of challenges reported in the literature when designing learning courses for Arabic users. Confirming the suitability of design guidelines for specific users' needs can be challenging in the context of the Arabic language. This is mainly due to the unique characteristics of this language, which contribute to users' satisfaction with the interface. This study evaluated the feasibility of using Arabic User Interface (UI) guidelines for tablet PCs. The UI guidelines were developed, evaluated, and refined using the Delphi technique. A total of six UI design experts were recruited for this study. The results revealed a number of guidelines that can be used in the design of Arabic UI. The proposed guidelines can standardise the design of Arabic UI by offering future directions on how to effectively apply design principles for tablet PCs.